Effects of an 8-week resistance-training protocol on jumping performance in national-level female volleyball players - Johnson, Q. R.; Kukic, F.; Todorovic, N.; Cuk, I.; Cvorovic, A.; Dawes, J. J. (Journal of Australian Strength and Conditioning, 2020)
Volleyball is a sport that requires multiple explosive effort jumps. Specifically, scoring performance (i.e.,, spiking and blocking) is centred on the jumping component of the game, which is generally reflective of an individualfs ability to sufficiently generate force and produce power. Thus, in an effort to enhance performance, it is of upmost importance to explore the relationships between strength development and its influence on jump ability. The purpose of this study was to determine the degree to which jump performance is influenced by an 8-week resistance-training protocol in national-level female volleyball players. The training protocol consisted of four components: 1.) muscular endurance, 2.) hypertrophy, 3.) maximal strength, 4.) maximal strength and explosive power. A secondary purpose was to provide both, the coach and athlete information on which areas of training should be emphasized. Thirteen (n = 13; age: 20.02 ± 3.95 years; height: 181.08} ± 8.17 cm; weight: 69.55 ± 10.07 kg) national league female volleyball players participated in this study and training program. Jump performance was assessed on three separate occasions via a squat jump (SJ), countermovement jump (CMJ), and countermovement jump with an arm swing (CMJa). Statistically significant (p . <= 0.05) improvements were observed from Pre-, Mid-, and Post-test, for the SJ and CMJ. Power and hypertrophy-based training approaches appeared to be the most beneficial for improving jump performance. Thus, if improving jump performance is an objective in athletes with a low training age, it is recommended that the S&C first focus on increasing muscle fibre size and hypertrophy-based training approaches before progressing to maximal strength and explosive power-focused training.